2017
DOI: 10.1590/18069657rbcs20160466
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Fertilization Increases Biomass and Nutrient Accumulation Under Improved Fallow Management in a Slash-and-Mulch System in Eastern Amazonia, Brazil

Abstract: Improvement of fallow vegetation can have a positive impact on the productivity of slash-and-mulch systems in eastern Amazonia. Phosphorus fertilization can increase biomass and nutrient stocks in the fallow phase, thereby improving nutrient cycling and crop productivity. Here, we compared biomass and nutrient stocks under three fallow management strategies: (1) natural fallow (regrowth vegetation) -NF; (2) NF vegetation improved with leguminous trees (Sclerolobium paniculatum Vogel and Inga edulis Mart.) -IF;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…During the final year of Rotation 1 (Year 9), however, although trees were still larger in the presence of P+K fertilization, there was no longer a significant effect on growth rates in most cases. This is consistent with other research from Eastern Amazonia that showed that P and/or K fertilization increased secondary forest growth [45,48]. The presence of the N-fixing I. edulis was not associated with increased growth, survival, or volume of any other planted tree species.…”
Section: Planted Tree Growthsupporting
confidence: 92%
“…During the final year of Rotation 1 (Year 9), however, although trees were still larger in the presence of P+K fertilization, there was no longer a significant effect on growth rates in most cases. This is consistent with other research from Eastern Amazonia that showed that P and/or K fertilization increased secondary forest growth [45,48]. The presence of the N-fixing I. edulis was not associated with increased growth, survival, or volume of any other planted tree species.…”
Section: Planted Tree Growthsupporting
confidence: 92%